Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa pada Materi Pembangunan dan Pertumbuhan Ekonomi Kelas XI MA. Muallimin Univa Medan Tahun Pelajaran - Nurhalija Pasaribu; Samio; Herdi; Rijal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of the problem-based learning model on students’ learning outcomes in the topic of economic development and growth in grade XI at MA Muallimin UNIVA Medan. The background of this research is the low student learning outcomes in economics, particularly on the topic of development and economic growth, which is caused by the lack of variation in teaching methods and limited student interaction. This research uses a true experimental design. The experimental design applied is the posttest-only control design. The research sample consists of grade XI students divided into an experimental class and a control class. The research instruments used were pretest and posttest. Data analysis techniques included normality test, homogeneity test, and hypothesis testing (t-test). The results show that the application of the problem-based learning model significantly improved students’ learning outcomes, with an average score in the experimental class of 68.33, which was higher than that of the control class, which scored 59.57. The research results showed an Fcount < Ftable value, namely 1.15 < 2.00. The hypothesis test results showed a significance value (2-tailed) of 0.002 < 0.05, which means H0 is rejected and Ha is accepted. This indicates that the problem-based learning model has an effect on students’ learning outcomes in the topic of economic development and growth. The conclusion of this study is that the problem-based learning model has a positive and significant effect on improving students’ learning outcomes in the topic of economic development and growth for grade XI students at MA Muallimin UNIVA Medan in the academic year 2024/2025.